Hong Kong in transition : one country, two systems - Ash, Robert F. (RoutledgeCurzon studies in the modern history of Asia, 2003)
This book offers a perspective on the constitutional and administrative experiment that has been taking place in Hong Kong, based on a substantial period under Chinese rule.